Lung Function Abnormalities in Sickle Cell Anaemia - Yvonne A. Dei-Adomakoh; Jane S. Afriyie-Mensah; Audrey Forson; Martin Adadey; Thomas A. Ndanu; Joseph K. Acquaye (Advances in Hematology)
Background. Abnormalities in lung function tests have been shown to commonly occur in a majority of patients with sickle cell disease (SCD) even at steady state. The prevalence and pattern of these lung function abnormalities have been described in other populations but this is unknown among our sickle cell cohort. There is generally little information available on risk factors associated with the lung function abnormalities and its relevance in patient care. Method. This was an analytical cross-sectional study involving 76 clinically stable, hydroxyurea-naive adult Hb-SS participants and 76 nonsickle cell disease (non-SCD) controls. A structured questionnaire was used to obtain sociodemographic data and clinical history of the participants. Investigations performed included spirometry, pulse oximetry, tricuspid regurgitant jet velocity (TRV) measurements via echocardiogram, complete blood counts, free plasma haemoglobin, serum urea, and creatinine. Results. Weight, BMI, mean FVC, and FEV1% predicted values were comparatively lower among the Hb-SS patients (p < 0.001). Abnormal spirometry outcome occurred in 70.4% of Hb-SS patients, predominantly restrictive defects (p < 0.001), and showed no significant association with steady-state Hb, WBC count, free plasma haemoglobin, frequency of sickling crisis, chronic leg ulcers, and TRV measurements (p > 0.05). The mean oxygen saturation was comparatively lower among Hb-SS patients (p < 0.001). Conclusion. Measured lung volumes were significantly lower in Hb-SS patients when compared to non-SCD controls and this difference was not influenced by anthropometric variance. Lung function abnormalities, particularly restrictive defects, are prevalent in Hb-SS patients but showed no significant association with recognized markers of disease severity.